1998
DOI: 10.1002/(sici)1097-0363(19980315)26:5<519::aid-fld630>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of flow through wavy-walled channels

Abstract: A numerical procedure is developed for the analysis of flow in a channel whose walls describe a travelling wave motion. Following a perturbation method, the primitive variables are expanded in a series with the wall amplitude as the perturbation parameter. The boundary conditions are applied at the mean surface of the channel and the first-order perturbation quantities are calculated using the pseudospectral collocation method. Although limited by the linear analysis, the present approach is not restricted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 24 publications
2
13
3
Order By: Relevance
“…The ow inside periodic, modulated channel or tube exhibits an abundance of interesting physics depending upon the modulation amplitude and frequency, and the ow rate of the passing uid. For Newtonian uid, numerical results and experimental ow visualizations showed that recirculation regions, often referred to as vortices, would form beneath the modulation crest beyond a certain critical Reynolds number that decreases exponentially as the modulation amplitude or the wavenumber increases [1,[12][13][14][15][31][32][33][34][35][36][37][38]. The size of the recirculation ow region as identi每ed by the distance between the separation and reattachment points varies with Reynolds number as Re increases beyond the critical Reynolds number.…”
Section: Introductionmentioning
confidence: 99%
“…The ow inside periodic, modulated channel or tube exhibits an abundance of interesting physics depending upon the modulation amplitude and frequency, and the ow rate of the passing uid. For Newtonian uid, numerical results and experimental ow visualizations showed that recirculation regions, often referred to as vortices, would form beneath the modulation crest beyond a certain critical Reynolds number that decreases exponentially as the modulation amplitude or the wavenumber increases [1,[12][13][14][15][31][32][33][34][35][36][37][38]. The size of the recirculation ow region as identi每ed by the distance between the separation and reattachment points varies with Reynolds number as Re increases beyond the critical Reynolds number.…”
Section: Introductionmentioning
confidence: 99%
“…This is not unexpected upon examination of the governing equation. As shown in Equations (5) and (6), terms that cause the time-dependency in flow diminish by increasing the gap and consequently, flow behaves as Couette flow between two parallel plates at wide gaps.…”
Section: Resultsmentioning
confidence: 99%
“…This work raises questions about the dissipation process and its role in such a flow. Selvaraja et al [10] develop a numerical procedure for examining the fluid motion during flow in a channel. The boundary conditions are applied at the mean surface of the channel and the primitive variables are inflated in a series with the wall amplitude as the perturbation parameter using pseudospectral collocation method the key attribute of this method is not restricted by the reynolds number of the flow and the wave number and frequency of the wavy-walled channel.…”
Section: Fig2 Contours Of Turbulence Intensity and A Dimensional Temmentioning
confidence: 99%